2015
DOI: 10.1177/1352458514558134
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic lesions in multiple sclerosis by 7T MRI: Clinical implications and relationship to cortical pathology

Abstract: Objective Pathology in both cortex and deep gray matter contribute to disability in multiple sclerosis (MS). We used the increased signal-to-noise ratio of 7-tesla (7T) MRI to visualize small lesions within the thalamus and to relate this to clinical information and cortical lesions. Methods 7T MRI scans were obtained on 34 MS cases and 15 healthy volunteers. Thalamic lesion number and volume were related to demographic data, clinical disability measures, and lesions in cortical gray matter. Results Thalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
8
48
1
Order By: Relevance
“…The significant decrease in FA and increase in MD within the thalamus in MSF seem not be attributable to typical MS lesions, which, in line with our results, have been recently reported not to occur frequently in RRMS patients in this region [29]. These results are also in agreement with the VBM analysis.…”
Section: Discussionsupporting
confidence: 95%
“…The significant decrease in FA and increase in MD within the thalamus in MSF seem not be attributable to typical MS lesions, which, in line with our results, have been recently reported not to occur frequently in RRMS patients in this region [29]. These results are also in agreement with the VBM analysis.…”
Section: Discussionsupporting
confidence: 95%
“…In-vivo research of lesions in other GM structures in relation to symptom development is sparse. A recent study with 7 T MRI, found thalamic lesions in 24 of 34 MS patients and thalamic lesion load correlated with EDSS and the 9HPT (Harrison et al, 2015).…”
Section: The Development Of Epileptic Seizures Was Better Understood mentioning
confidence: 97%
“…Furthermore, with the advent of more powerful MRI scans, the confirmation of involvement of the gray matter became more sensitive. Harrison et al 25 conducted a study with 34 patients and demonstrated through 7-Tesla MRI scan that thalamic lesions were present in 24 patients. It is known that such lesions are associated with a higher EDSS score, cortical lesions and progressive forms.…”
Section: Discussionmentioning
confidence: 99%